Studi Literatur Implementasi Sertifikasi Halal Produk UMKM - Fuadi; Andri Soemitra; Zuhrinal M. Nawawi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to analyze the implementation of halal product guarantees on MSMEs in Indonesia. The data used in the analysis related to the research topic were taken from various literature, both from books and journal articles. Data from various sources were then analyzed using a literature review approach. Based on the analysis, it was found that the halal food sector is currently a new opportunity to increase growth and economic development. It is said to be a new opportunity because not only Muslim-majority countries but Muslim-minority countries also take part in the development of the halal industry. Therefore, the Indonesian government is also trying to develop the domestic halal food and beverage industry to encourage the growth of the halal industry. In promoting the application of halal standards where one of the things needed is halal certification, Law Number 33 of 2014 concerning Halal Product Guarantee is issued, Article 4 states that halal product certification is mandatory. The method used in this research is library research. The literature study in this research was conducted to study the definition of keywords, to deepen theories and concepts, and to identify variables related to the background and context of the research. Literature studies related to the analysis of barriers to halal product, the journal uses a search application or search application that is searched on Google Scholar with the keyword